Ностальгия по Логосу: поэзия Ивана Жданова в контексте неотрадиционализма - Edyta Anna Fedorushkov (Studia Rossica Posnaniensia)
The paper aims at presenting an attempt to interpret Ivan Zhdanov’s poetry in the context of neotraditionalism. This literary project, founded by Valery Tiupa, is based on the idea of dialogue by Mikhail Bakhtin as well as philosophy of personalism by Martin Buber, Nikolai Berdyaev, Emmanuel Levinas. In contrast to postmodernism, neotraditionalism takes an attempt to restore the value and esteem to widely understood cultural tradition (especially Mediterranean and Christian cultures).